Delimitation of the Continental Shelf in the Central Arctic Ocean: Is It Possible Nowadays? - Koshkin, Valentin (Arctic Review on Law and Politics, 2022)
Russia was the first Arctic coastal state to make an official submission to the Commission on the Limits of the Continental Shelf (CLCS) in 2001. The purpose of Russia’s submission was the delineation of the outer limits of the continental shelf beyond 200 nautical miles in the Arctic Ocean in accordance with UNCLOS Article 76. The area claimed by Russia is a large portion of the seabed extending even to the exclusive economic zones of Denmark and Canada. However, Russia’s actions regarding delineation in the Arctic Ocean have led to criticism from several Russian experts in the field of international law. This paper is a response to a series of articles by Ivan Zhudro and Alexander Vylegzhanin. It argues against their assertion that Russia and the other Arctic states could have established the outer limits of their continental shelf in the absence of CLCS recommendations through the delimitation procedure in accordance with UNCLOS Article 83. The article rejects the argument that during the delimitation the Arctic states could have used meridian lines (sectors) to exclude the existence of an international seabed area in the Central Arctic Ocean. The author challenges the position that the result of delineation under UNCLOS Article 76 would not be fair since the US has not ratified UNCLOS.